2018
DOI: 10.3144/expresspolymlett.2018.88
|View full text |Cite
|
Sign up to set email alerts
|

Desiccant effect of starch in polylactic acid composites

Abstract: Polylactic acid (PLA)/starch and PLA/starch-glycerol composites with different glycerol contents were prepared in a wide composition range, in order to study their applicability as packaging materials for dry products. Water uptake was determined at a temperature of 23°C and different relative humidities. Structure and mechanical properties were also investigated. PLA/ unplasticized starch composites could absorb a considerable amount of water. As a result, they may be adequate as a biodegradable inner contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The water absorption of starch is attributed to the hygroscopic nature of the polysaccharide. This result is similar to those in [33][34][35][36][37].…”
Section: Water Absorptionsupporting
confidence: 89%
“…The water absorption of starch is attributed to the hygroscopic nature of the polysaccharide. This result is similar to those in [33][34][35][36][37].…”
Section: Water Absorptionsupporting
confidence: 89%
“…The work of [17] on the extrusion of PLA–starch showed that the interdependence of starch and PLA increased with a decrease in starch percentage, especially when the ratio of starch to PLA is less than 1:10 and the water absorption was reduced. The reinforcing effect of starch is established in [20], where work on PLA–starch using glycerol as a plasticizer and a compression molding method were performed. The stiffness and strength of the composite were enhanced with the use of a plasticizer.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, numerous papers can be found about the utilization of bio-based as well as renewable, natural polymers in blends and composites. Bio-polyethylene [1,2], starch [3][4][5][6], protein [7,8] and lignin [9][10][11][12][13][14] have been used as a matrix or dispersed component of blends, while cellulose [15][16][17][18], chitin [5,19] and lignocellulose [4,9,[20][21][22][23][24] have been applied as a reinforcement in composites. In addition, the advantageous properties of bio-based polymers and natural fibers were combined in their composites in several cases [1,18,24].…”
Section: Introductionmentioning
confidence: 99%